Efficiency Indexes in Resource Mobilization: A Study of Andhra Pradesh State Financial Corporation (APSFC) - Viswanatha Reddy, C. (Indian Journal of Finance, 2013)
Capital structure represents the mix of different sources of long-term funds in the total capitalization. Optimal capital structure is a financing-mix which maximizes the firms’ value/the shareholders’ wealth or minimizes its overall cost of capital. An appropriate capital structure acts as the basis for sound operations of a State Financial Corporation. The resource mix of APSFC mainly consists of equity share capital, reserves, bonds and debentures, refinancing from the IDBI and the RBI, and loans in lieu of share capital, and so forth. Linking the borrowing powers with equity as per the provisions of the SFCs Act helps in the potentiality of the Corporation in lending operations. The Corporation heavily depends on debt finance by issuing bonds and debentures. A high degree of debt component in capital structure increases the risk and may lead to financial distress in adverse times. A high cost of funds employed makes it very difficult to improve the profitability of the Corporation. Normally, the cost of bond financing of the Corporation is cheaper as compared to raising funds through equity because interest on debt is allowed as an expense for tax purposes. Therefore, a good and complete exercise on resource planning for short-term as well as long-term periods is a need of utmost importance for the Corporation in order to cater to the growing financial needs of industrial concerns. The present paper focuses on measuring the efficiency of the Corporation in terms of its resource mobilization. Some important aspects for measuring the efficiency of resource mobilization are examining the - trends in resources and sanctions by the Corporation, cost of various sources of funds, cost of debt funds, weighted average cost of capital (LME-Index), and equity multiplier. The paper also provides some viable and useful suggestions to fine tune the performance of the Corporation for efficient fund management by the APSFC.